Applications of FAPI PET/CT in the diagnosis and treatment of breast and the most common gynecologic malignancies: a literature review - Li, Tengfei; Zhang, Jintao; Yan, Yuanzhuo; Tan, Min; Chen, Yue (Frontiers in Oncology, 2024)
The fibroblast activating protein (FAP) is expressed by some fibroblasts found in healthy tissues. However, FAP is overexpressed in more than 90% of epithelial tumors, including breast and gynecological tumors. As a result, the FAP ligand could be used as a target for diagnosis and treatment purposes. Positron emission tomography/computed tomography (PET/CT) is a hybrid imaging technique commonly used to locate and assess the tumor’s molecular and metabolic functions. PET imaging involves the injection of a radiotracer that tends to accumulate more in metabolically active lesions such as cancer. Several radiotracers have been developed to target FAP in PET/CT imaging, such as the fibroblast-activation protein inhibitor (FAPI). These tracers bind to FAP with high specificity and affinity, allowing for the non-invasive detection and quantification of FAP expression in tumors. In this review, we discussed the applications of FAPI PET/CT in the diagnosis and treatment of breast and the most common gynecologic malignancies. Radiolabeled FAPI can improve the detection, staging, and assessment of treatment response in breast and the most common gynecologic malignancies, but the problem with normal hormone-responsive organs remains insurmountable. Compared to the diagnostic applications of FAPI, further research is needed for future therapeutic applications.